PENERAPAN MODEL PEMBELAJARAN STAD DAN DISCOVERY LEARNING BERBANTUAN MACROMEDIA FLASH UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Dewi Syafriani; Siti Aminah Br Bancin (Universitas Negeri Medan, 2020)
This study aims to determine learning outcomes using the Student Team Achievement Divisions (STAD) model assisted with macromedia flash compared to Discovery Learning assisted with macromedia flash on the reaction rate material. The study population was all students of class XI MIPA MAN 3 Medan. The sampling technique in this study is simple random sampling. The selected sample is Class XI MIPA 1 as an experimental class I which is treated with a Student Team Achievement Divisions (STAD) model assisted by macromedia flash and Class XI MIPA 3 as an experimental class II which is treated with a Discovery Learning model assisted by macromedia flash. This study uses test instruments that have been tested and are valid. Student learning outcomes data are first tested for normality and homogeneity, where the results obtained by both groups of samples are homogeneous and normally distributed. Hypothesis testing uses the Independent Sample T-Test, with the results of the research obtained a significance value of 0.047. Thus, there are significant differences in student learning outcomes taught using the Student Team Achievement Divisions (STAD) model with Discovery Learning assisted by macromedia flash with a result of 14% using the STAD model better than Discovery Learning.Keywords: Learning Outcomes, Student Collaboration, Student Team Achievement Divisions (STAD), Discovery Learning, Reaction Rate